Our farming future - Commission of the European Communities (Luxembourg : Office for Official Publications of the European Communities ; [Washington, DC : Commission of the European Communities [distributor], 1993)
This book highlights how the security of food supply should be a matter of concern around the world. This concerned led to the European community to create a single market in agriculture as early as 1962.
Issued also in Danish, Dutch, French, German, Greek, Italian, Portuguese and Spanish.
ahz 18/03/2019
Loans
Keywords: Agriculture and state; Agriculture